Moxibustion is an Alternative in Treating Knee Osteoarthritis: The Evidence From Systematic Review and Meta-Analysis. Issue 6 (February 2016) - Song, Guo-Min; Tian, Xu; Jin, Ying-Hui; Deng, Yong-Hong; Zhang, Hui; Pang, Xiao-Li; Zhou, Jian-Guo
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Knee osteoarthritis (KOA) is a common disorder in elderly. There is no known cure for KOA, and thus therapeutic strategies of alleviating symptoms are increasingly emphasized. Moxibustion has been widely used to treat KOA; however, results are inconclusive. The aim of our study is to critically reassess the effects of moxibustion on KOA. We searched PubMed, EMBASE, Cochrane Central Register of Controlled Trials (CENTRAL), and Chinese Biomedical Literature database (CBM) through 25 November 2015. Two independent reviewers selected studies and abstracted information, as well as assessed the risk of bias using Cochrane risk of bias tool. The random-effects meta-analyses were performed based on abstracted data. We initially captured 163 citations and added 4 records through checking review. After critical appraisal, 13 RCTs were included. Meta-analyses indicated that moxibustion is not statistically different from oral drug in improving the response rate (MD = 1.09; 95% CI = 1.00, 1.20; P = 0.05), alleviating pain and improving physical function. Our meta-analysis also found that moxibustion is superior to usual care and sham moxibustion in reducing WOMAC score (MD = 7.56; 95% CI = 4.11, 11.00; P = 0.00), pain and function, as well as increasing QoL. Moreover, most AEs caused by moxibustion can heal without medical care. We concluded that moxibustion treatment is equal to the oral drugs and intra-articular injections and may be an alternative in treating patients with KOA.